Reanalysis of the German PISA Data: A Comparison of Different Approaches for Trend Estimation With a Particular Emphasis on Mode Effects - Robitzsch, Alexander; Lüdtke, Oliver; Goldhammer, Frank; Kroehne, Ulf; Köller, Olaf (Frontiers in Psychology, 2020)
International large-scale assessments, such as the Programme for International Student Assessment (PISA), are conducted to provide information on the effectiveness of education systems. In PISA, the target population of 15-year-old students is assessed every three years. Trends show whether competencies have changed in the countries between PISA cycles. In order to provide valid trend estimates, it is desirable to retain the same test conditions and statistical methods in all PISA cycles. In PISA 2015, however, the test mode changed from paper-based to computer-based tests, and the scaling method was changed. In this paper, we investigate the effects of these changes on trend estimation in PISA using German data from all PISA cycles (2000 to 2015). Our findings suggest that the change from paper-based to computer-based tests could have a severe impact on trend estimation but that the change of the scaling model did not substantially change the trend estimates.